International Evidence on the Demand for Money - Fair, Ray C. (The Review of Economics and Statistics, 1987)
One of the current questions in the literature on the demand for money is whether the adjustment of actual to desired money holdings is in nominal or real terms.This paper describes a simple procedure than can be used to test the nominal against the real hypothesis.The test is carried out for 27 countries.The paper also tests the structural stability of the demand for money equations and the correctness of the dynamic specification.The results are strongly in favor of the nominal adjustment hypothesis.The estimated equations are quite good in terms of the number of coefficient estimates that are of the right sign and that are significant.The equations also stand up well when tested against a more general dynamic specification.There is, however, some evidence of structural instability before and after 1973, although the instability is generally moderate.The instability does not affect the conclusion that the nominal adjustment hypothesis dominates the real adjustment hypothesis.